Scapegoating Islam: intolerance, security, and the American Muslim - Thomas, Jeffrey L. (Praeger, 2015)
America's evolving perspectives on Islam: from threat abroad to challenge at home -- 9/11 and the new Homeland Security paradigm -- Homeland Security and the Muslim experience at the state and local levels -- Climate of fear -- Hate crimes and anti-Muslim violence -- Muslim Americans and the Homeland Security enterprise -- Aligning security and civil rights -- Timeline of major policies and government actions affecting Muslims in America